2015
DOI: 10.1038/srep11628
|View full text |Cite|
|
Sign up to set email alerts
|

Musical training, individual differences and the cocktail party problem

Abstract: Are musicians better able to understand speech in noise than non-musicians? Recent findings have produced contradictory results. Here we addressed this question by asking musicians and non-musicians to understand target sentences masked by other sentences presented from different spatial locations, the classical ‘cocktail party problem’ in speech science. We found that musicians obtained a substantial benefit in this situation, with thresholds ~6 dB better than non-musicians. Large individual differences in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
128
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 52 publications
15
128
3
7
Order By: Relevance
“…The musicians showed overall better intelligibility than non-musicians, confirming a musician advantage for speech-on-speech perception. In contrast to many of the previous studies (Parbery-Clark et al, 2009;Fuller et al, 2014b;Ruggles et al, 2014;Boebinger et al, 2015), but in line with one study on informational masking (Swaminathan et al, 2015), this effect was strong and robust across all voice conditions. Hence the results confirmed that indeed the musician advantage for better speech perception may strongly depend on a specific task where the task relies on skills that are improved by musical training (also in line with Fuller et al, 2014b), such as better pitch perception or stream segregation.…”
Section: Discussioncontrasting
confidence: 54%
“…The musicians showed overall better intelligibility than non-musicians, confirming a musician advantage for speech-on-speech perception. In contrast to many of the previous studies (Parbery-Clark et al, 2009;Fuller et al, 2014b;Ruggles et al, 2014;Boebinger et al, 2015), but in line with one study on informational masking (Swaminathan et al, 2015), this effect was strong and robust across all voice conditions. Hence the results confirmed that indeed the musician advantage for better speech perception may strongly depend on a specific task where the task relies on skills that are improved by musical training (also in line with Fuller et al, 2014b), such as better pitch perception or stream segregation.…”
Section: Discussioncontrasting
confidence: 54%
“…Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here. On the other hand, we found no gains in rapid naming or phonological memory, despite the fact that both reading (46)(47)(48)(49)(50) and verbal memory (30)(31)(32)(33)(34)(35)(36)(37)(38) have been associated with music training in other studies, suggesting either that the training studied here was not optimally designed to enhance these skills or that enhancing these skills requires a greater amount of training or training begun earlier in life. A third possibility is that the link between phonological processes and beat synchronization is restricted to phonological awareness.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies comparing nonmusicians with musicians who began training early in life have revealed a "signature" set of enhancements associated with musical experience (27,28). Relative to nonmusician peers, musicians tend to show enhanced speech-innoise perception (29)(30)(31)(32)(33)(34), verbal memory (30)(31)(32)(33)(35)(36)(37)(38), phonological skills (39)(40)(41)(42)(43)(44)(45), and reading (46-50), although not without exception (51,52). Music training has also been linked to enhancements in the encoding of sound throughout the auditory system.…”
mentioning
confidence: 99%
“…Although these findings provide hints to a general consistency within musical tasks, no transfer or relationship to tasks outside the musical domain was observed here, because performance in verbal WM was not related to any other of the WM tasks. Future research may further test verbal and other nonmusical tasks in highly trained experts (see Parbery-Clark et al, 2009;Ruggles et al, 2014;Swaminathan et al, 2015). However, our results suggest that musical training did not enhance all cognitive skills, nor was it related to self-selection into the chosen profession.…”
Section: Discussioncontrasting
confidence: 39%